Training on Vegetable Cultivation Using the Hydroponic Method to Increase Household Income in Timbuseng Village - Andi Nursiah; Sulfiana; Ida Suryani; Musdalipa (Masterpiece, 2025)
The limited availability of land, low financial capacity, and minimal agricultural investment are significant challenges faced by young farmers. In response, hydroponic vegetable cultivation presents an innovative and efficient solution, allowing crops to be grown without requiring large areas of land or substantial capital. This method is particularly advantageous for urban and semi-urban communities where space constraints limit traditional farming practices. This community service program aims to enhance household income by promoting simple hydroponic vegetable farming as a sustainable agricultural practice. The implementation method consists of structured training and practical application, where participants learn fundamental hydroponic concepts, including seed sowing, nutrient management, and plant maintenance. Through hands-on experience, participants gain the necessary skills to establish and manage small-scale hydroponic systems in their home environments. The results of the program show a positive response from the community, with many participants successfully applying their newly acquired knowledge to start home-based hydroponic vegetable cultivation. This initiative contributes to household food security while also creating opportunities for additional income generation. By efficiently utilizing available space, community members can produce fresh vegetables for both personal consumption and local markets, supporting economic resilience and sustainable agricultural development.